2012
DOI: 10.1590/s1517-70762012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cytotoxicity of polyurethane and non-latex orthodontic chain elastics

Abstract: Allergy caused by latex proteins has been well documented. Thus, the study of non-latex materials, is necessary. The aim of this study is to evaluate the cytotoxicity of silver-coloured orthodontic chain elastics, of polyurethane and latex-free. Nine chain elastics from different manufactures (3 latex-free and 6 polyurethane) were divided into 9 groups of 10 elastics each: Group UK (Latex-free, 3M Unitek), Group TP (Látex-free, TP Orthodontics), Group AO (Látex-free, American Orthodontics), Group O (Polyuretha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…As for the long‐term cytotoxicity of FPHU, it might be due to some low molecular weight components in PU dissolved in the extract. This was consistent with other reports that PUs had a release of toxic ingredients at 48 h . If possible, GPC is a very suitable method to remove the low molecular weight components.…”
Section: Resultssupporting
confidence: 92%
“…As for the long‐term cytotoxicity of FPHU, it might be due to some low molecular weight components in PU dissolved in the extract. This was consistent with other reports that PUs had a release of toxic ingredients at 48 h . If possible, GPC is a very suitable method to remove the low molecular weight components.…”
Section: Resultssupporting
confidence: 92%
“…Spectrophotometric essay allows rapid and reliable evidence for cell viability to be obtained based on the use of vital stain incorporated by viable cells [23][24]. Dead or damaged cells cannot incorporate vital stain, thus not being recognized on optical reading.…”
Section: Discussionmentioning
confidence: 99%
“…These results agreed with previous reports that polyurethanes may release toxic ingredients within 1-2 days in prepared extracts. 12 In this case, the slight cytotoxicity might come from complex factors. For example, when WPU dispersion was prepared, TEA was added to neutralize the carboxylic groups of DMPA.…”
Section: Mtt Assay and Morphological Observation Of Cells Cultured On...mentioning
confidence: 99%
“…9 WPU retains the excellent exibility of polyurethanes, but is also low toxic, non-polluting, low cost, and has good applicability and safety, 10 properties that are highly appreciated in the eld of tissue engineering; 2 however, it has been reported that WPU displayed slight cell toxicity and slow degradation rate. [11][12][13][14] In view of the extensive application as a tissue engineered scaffold, the cytocompatibility and biodegradability of WPU should be enhanced. The performance of cells attached to materials is mainly affected by the surface hydrophilicity/hydrophobicity, roughness, and microstructure of the materials.…”
Section: Introductionmentioning
confidence: 99%